PERAN DISIPLIN KERJA PENDIDIKAN DAN KOMITMEN TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENNING (Studi Kasus di Desa Laprak, Desa Sumbersuko, Desa Pandak dan Desa Klampokan Kecamatan Klabang Kabupaten Bondowoso) - Hariyanto, Hariyanto; Sari, Lita Permata; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The aim of this research is to analyze the influence of variablesThe Role of Educational Work Discipline and Commitment to the Performance of Village Officials with Job Satisfaction as an Intervening Variable (Case Study in Leprak Village, Sumbersuko Village, Pandak Village, and Klampokan Village, Klabang District, Bondowoso Regency). By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application. Work discipline has a significant positive effect on job satisfaction Education has a significant positive effect on job satisfaction, Commitment has a significant positive effect on job satisfaction, Work discipline has a significant positive effect on performance, Education positive but not significant effect on Performance, Commitment has a significant positive effect on Performance, Job satisfaction has a positive but not significant effect on Performance, Work discipline has a positive but not significant effect on Performance through Job Satisfaction, Education has a positive but not significant effect on Performance through Job Satisfaction, and Commitment has a positive but not significant effect on Performance through Job Satisfaction.